A mixed-method analysis to identify the current focus, trends, and gaps in health science research in Saudi Arabia - AL-Shammary, Asma Ayyed; Hassan, Sehar un-Nisa; Alshammari, Fahad Saud; Alshammari, Modi Rataan Rifai (Frontiers in Public Health, 2023)
Background: The identification of current gaps in high-impact medical research in Saudi Arabia has international significance due to the trend of collaborative research in the field of health and medicine and the focus on knowledge-sharing. The purpose of this study is to assess the current focus, gaps, and priorities in population health research in Saudi Arabia. Methods: We employed a mixed-method research approach to achieve research objectives. (1) a systematic review of scientific research studies that are published between Jan 2020 to Jan 2022 in the top fifty Q1 medical science journals (2) a cross-sectional survey collected data from professionals employed in various organizations including the Ministry of Health (MoH), Ministry of Education (MoE), health organizations and universities, and the health industry. The close-ended survey questions inquired about the broad and specific areas of ongoing health research projects by these researchers and organizations in Saudi Arabia. Results: The literature search on databases identified Science Direct (n = 741), Pub Med (n = 244) and Google Scholar (n=1,5600). After screening according to the inclusion/exclusion criterion, (n=26) original studies were selected for detailed evaluation and synthesis. Among these (n=7) studied infectious diseases, (n=7) cancer and cardiac disease (n=5). These studies focused on the etiology, treatment management and therapy outcomes of these health conditions. The survey was completed by (n=384) respondents from these organizations. Most of the ongoing research projects focus on clinical sciences (27%) followed by basic sciences (24%) and public health research (24%) and a limited number of researchers were involved in healthcare management (2%) and informatics (2%). Most research focused on kidney and liver disorders (80%), obesity (74%), diabetes (74%), hormonal diseases (64%), and infectious disease (66%); it is equally important to design and fund research in some of the neglected areas including reproductive health (3%), physical and mental disabilities (1%). Conclusion: Findings suggest that current gaps in original research from Saudi Arabia are in healthcare service quality, reproductive health, physical and mental disabilities and health informatics. Researchers and funding agencies and international collaborative projects should prioritize these areas.